The influence of chosen socio-demographic factors on life quality of the stroke patients - introductory research - Zawadzka, Justyna; Bejer, Agnieszka; Kwolek, Andrzej (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim: The aim of the paper was to evaluate the influence of chosen socio-demographic factors (age, gender, marital status, place of residence, source of income, housing conditions) on quality of life of stroke patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: Research included 60 patients after their first hemispheric stroke treated in 2012 at the rehabilitation ward of a provincial hospital. The measurement of quality of life was conducted by means of the Polish version of Stroke-Specific Quality of Life Scale which enables obtaining the profile of quality of life within twelve subscales and general quality of life. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: Quality of life after stroke deteriorates significantly with age (rS = - 0,395; p<0,001). People who are professionally active show the best quality of life ( x = 4,04), so the source of income influences the quality of life strongly (F = 7,293; p<0,001). The housing conditions of the subjects also influence the quality of life strongly (F = 3,715; p<0,05). The better the housing conditions (average x = 2,77; good x = 2,96; very good x = 3,69), the better the quality of life. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The quality of life of stroke survivors depends on the age, housing conditions and the source of living. Gender and place of living do not influence the quality of life of the subjects in any of the surveyed areas.